Evaluation of Bilingual Mathematics Learning Program at Al-Azhar Islamic Middle School, South Tangerang - Dwi Apriliani; Budi Manfaat; Arif Muchyidin (MASI Mandiri Edukasi, 2022)
This study evaluates the bilingual mathematics learning program at SMP Islam Al-Azhar 25, South Tangerang. The evaluation model used is CIPP (Context, Input, Process, Product). Data collection techniques using interviews, observation, and document analysis. The evaluation results show that the bilingual mathematics learning program at SMP Islam Al-Azhar 25 South Tangerang has been running well. The program aims to follow the school's